Effectiveness of Laser and Conventional Acne Treatments: Their Impact on Patient Satisfaction and Self-Confidence - Ginting, Indra; Mukhali, Hassan Basri Bin; Abas, Mohd Ihsanuddin Bin; Bayu Aji, Andreas; Dakhi, Tiwanto; Syafitri, Rachelli Nova; Rudang, Singgar Ni (Jurnal Perilaku Kesehatan Terpadu, 2024)
Background: Acne can affect patient confidence and satisfaction with treatment. Topical and systemic therapies, compared to more modern laser therapies, still occur in terms of effectiveness and patient satisfaction. Objective: This study compares the two methods and their impact on patient satisfaction and quality of life. Material and Method: This study compared acne vulgaris patients who underwent topical, systemic, and laser treatments. The efficacy of acne treatments was evaluated using the CADI (Cardiff Acne Disability Index) and the Visual Analogue Scale (VAS). The results showed that laser therapy patients reported significantly higher satisfaction and quality of life than those who underwent conventional treatment. Conclusion: This study shows that laser therapy is more effective than conventional treatments in reducing acne severity, and increasing patient satisfaction, and improving self-esteem. This confirms that laser therapy is a superior treatment option for patients who want faster results with better psychosocial outcomes.